Optimal Timing of Ovulation Triggering to Achieve Highest Success Rates in Natural Cycles—An Analysis Based on Follicle Size and Oestradiol Concentration in Natural Cycle IVF - Helmer, Anja; Magaton, Isotta; Stalder, Odile; Stute, Petra; Surbek, Daniel; von Wolff, Michael (Frontiers in Endocrinology, 2022)
Introduction Timing of ovulation triggering is essential in infertility treatments including treatments based on natural menstrual cycles. However, data on follicle size and estradiol (E2) concentration are limited. Therefore, the model of natural Cycle IVF (NC-IVF) was applied to provide more detailed information on these parameters to better schedule the optimal time for triggering ovulation. Materials & Methods Retrospective cross-sectional analysis of 606 monofollicular NC-IVF cycles performed at a university-based IVF centre from 2016 to 2019. Follicle size, E2 and LH serum concentrations were evaluated on day -5 to 0 (day 0 = day of oocyte retrieval). Ovulation was triggered if follicle size was 14-22mm. Patients with irregular cycles, endometriosis >II°, cycles with azoospermia or cryptozoospermia and cycles with inconsistent data were excluded. All parameters were analysed inter- and intraindividually and associations of the parameters were evaluated. Associations were adjusted for age, cause of infertility and number of previous transfers. Results Mean age of women undergoing NC-IVF was 35.8 ±4.0 years. Follicle size increased by 1.04 ±0.03 mm and E2 concentration by 167 ±11.0 pmol/l per day. Based on a multivariate adjusted mixed model with follicle size, E2 and their interaction, the number of retrieved oocytes was associated with E2 concentration (aOR 1.91, 95% CI: 1.03-3.56; p=0.040). Maturity of oocytes was associated not only with E2 concentration (aOR 2.01, 95% CI: 1.17-3.45; p=0.011) but also with follicle size (aOR 1.27, 95% CI: 1.01-1.60; p=0.039), as was the interaction of both parameters (aOR 0.96, 95% CI: 0.93-0.99; p=0.017). LH surge was calculated to start in 25% of cases at an E2 level of 637 pmol/l, in 50% of cases at 911pmol/l and in 75% of cases at an E2 level of 1480pmol/l. Live birth rate per follicle aspiration cycle was (non-significantly) higher in cycles with follicles sizes at the time of oocyte retrieval of 18-22mm (7.7-12.5%) versus in cycles with follicles sizes of 14-17 mm (1.6-4.3%). Conclusion The study contributes to an optimisation of infertility treatments involving natural cycles. The study gives guidance about the number of days required after follicle monitoring to schedule the optimal time for triggering ovulation.